Eksperimen Model Pembelajaran Discovery Learning Berbasis Assessment For Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Tingkat Kreativitas Siswa Kelas VII Di SMP Muhammadiyah 1 Kartasura - Ermawati, Reny Tri; , Muhammad Noor Kholid, S.Pd., M.Pd (2017)
This study aimed to analyze: (1) differences in the effect of the application of learning model Discovery earning-based Assessment For Learning, Discovery Learning, and Expository the learning outcomes of mathematics, (2) differences in the effect of the level of creativity of mathematical students' learning outcomes mathematics, (3) the interaction between application-based learning model Discovery learning sessment For learning, Discovery learning, and Expository with mathematical creativity level of the mathematics learning outcomes. This research was quantitative with quasi-experimental research design. The population in this study were all students of class VII SMP Muhammadiyah 1 Kartasura 2016/2017. The sampling technique in this study using cluster random sampling.Methods of data collection using documentation, questionnaire, and test results of learning. Data were analyzed using two-way analysis of variance with different cells. The results of the analysis with a significance level of 0.05 indicates that: (1) there are differences in the influence of the learning model based Discovery Learning Assessment For Learning, Discovery Learning, and Expository the mathematics learning outcomes with Fa = 6.32429 (2) there are differences in the influence of the mathematical creativity students 'mathematics learning outcomes with Fb = 22.16647 (3) there is no interaction between the learning model based Discovery learning Assessment For learning, Discovery learning, and Expository with the level of students' mathematical creativity to mathematics learning outcomes with Fab = 1.13083. Keywords: assessment for learning, discovery learning, creativity, learning outcomes mathematics